A thirty year perspective on posterior wall fractures of the acetabulum: Enigma or just another intra-articular. Issue 3 (June 2016) - Moed, Berton R.
الملخص: يحصل الباحثون المتعاملون مع أعداد صغيرة نسبيا من المرضى المصابين بكسور في الجدار الخلفي للحُق٬ على نتائج غير مرضية تقدر بـ ٣٠٪. فأدى المنطق إلى التصور بأن هذا النوع من الكسور يلتئم بصورة أسوأ من الكسور الحُقية الأخرى. لذا فإن أهم ماينبغي الإجابة عليه عند التعامل مع هذه الإصابات هو: (١) كيف يمكن تحديد نوعية العلاج٬ أهو جراحي أم غير جراحي؟ (٢) وهل يمكن تحسين تثبيت الكسور المفتتة وشظايا الكسور المنحشرة طرفيا. (٣) وما هي عوامل الخطورة المتسببة في نتائج سلبية بعد تثبيت الكسور جراحيا. (٤) وماهي النتائج السريرية والوظيفية المتوقعة بعد العلاج الجراحي. تمت مراجعة خبرتي العملية الطويلة في مجال دراسة كسور الجدار الخلفي للحُق، التي نُشرت خلال فترة زمنية طويلة للإجابة على هذه التساؤلات. وكانت الإجابات كالتالي: (١) فحص الضغط الديناميكي تحت التخدير هو الطريقة الوحيدة التي يمكن الاعتماد عليها لتحديد استقرار مفصل الورك. (٢) ومن الممكن تحسين تثبيت الكسور المفتتة وشظايا الكسور المنحشرة طرفيا باستخدام بناء تثبيتي ذي مستويين بالإضافة إلى طريقة غير تقليدية لأنماط معينة من الكسور. (٣) وفي كبار السن٬ التأخر في إعادة الورك المخلوع إلى مكانه٬ والكسور المفتتة٬ يكونان مصحوبان بنتائج سريرية غير جيدة. ويمكن التنبؤ بالنتيجة السريرية النهائية من دقة إعادة المفصل جراحيا (٤) بالإمكان توقع نتائج من جيدة إلى ممتازة لوظيفة الورك في نسبة عالية من هؤلاء المرضى٬ غير أنه قد يتبقى بعض العجز الوظيفي. Abstract: Investigators dealing with a relatively small number of patients with posterior wall fractures have found unsatisfactory clinical outcomes, estimated to be approximately 30%. Consequently, conventional wisdom has professed that these fractures do poorly relative to other acetabular fracture types and are somehow different. The main questions to be answered in the treatment of these injuries include: (1) how can the need for operative versus non-operative treatment best be determined, (2) can the fixation of comminuted and marginally impacted fracture fragments be improved, (3) what are the risk factors for an adverse outcome after operative fracture fixation, and (4) what are the expected clinical and functional outcomes after operative treatment? A review of my long-term body of work investigating posterior wall fractures of the acetabulum, published over an extended period of time, was conducted to address these questions. Answers to the proposed questions are as follows: (1) dynamic stress examination under anaesthesia is the only reliable way to determine hip joint stability; (2) fixation of comminuted and marginally impacted fracture fragments can be improved by using a two-level fixation construct, as well as a non-traditional surgical approach for certain fracture patterns; (3) delayed reduction of hip dislocation and comminuted fractures in older patients are associated with poor clinical outcome and the accuracy of surgical reduction is highly predictive of clinical outcome; and (4) good-to-excellent hip function should be expected in a high percentage of these patients. However, residual functional deficits may still remain.